Geleneksel türk tatlısı baklavayı çikolata ile birleştiren lezzet: damak baklava - FEYZİOĞLU, AHMET (My University, 2022)
Baklava, geleneksel Türk mutfağının vazgeçilmez tatlılarından biridir. Türk Standartları Enstitüsü‟ne göre “Türk Baklavası”nın tanımı; içinde un, yumurta, tuz, su ve niĢasta olan hamurun tekniğe uygun açılarak içine ya da arasına kaymak, tereyağ ya da tereyağdan elde edilmiĢ sade yağın ve çeĢidine göre antepfıstığı içi, ceviz içi, fındık içi ya da badem içi eklendikten ve kesildikten sonra uygun sıcaklık ve sürede piĢirilmiĢ, son olarak toz Ģeker ve limon suyu ya da limon tuzu eklenmiĢ suyun kaynatılması ile elde edilen Ģerbetin ilave edilmesi ile elde edilen üründür. Çikolata ise; temelinde kakao yağı, kakao kitlesi, Ģeker ve çeĢidine göre süt ürünlerinin tozlarından oluĢan tatlı bir gıdadır. Çikolata marketinde ürünü farklılaĢtıracak olan etmenlerden ilk akla gelen bu ana hammaddelerin doğru kombinasyonları ile reçetelendirilmesi, sonrasında bu reçete çikolata haline geldiğinde farklı çeĢnilerin belirli oranlarda eklenmesi düĢünülebilir. Marketteki ürünlerin geneline baktığımızda çeĢni olarak kullanılan ürünlerin baĢında fındık, fıstık, badem gibi yemiĢler gelmektedir. Damak markası, tüketicilerin nezdinde Antep fıstığı ile birleĢmiĢ, premium algısı yüksek bir markadır. Baklava dendiğinde akla ilk gelen çeĢnilerden olan Antep fıstığı, Damak markası ve baklava arasındaki bağı oluĢturmaktadır. Projede bu bağı kullanarak, tüketicilere baklava yeme deneyimini hissettirecek çeĢni ve hammaddeler kullanılarak çikolatalı bir tatlı sunulmuĢtur. Yapılan çalıĢmada öncelikle çeĢni ve hammaddeler belirlenerek ön numuneler hazırlanmıĢtır. Sonrasında ürünün raf ömrü testleri yapılmıĢtır. BelirlenmiĢ olan yeni çeĢni tedarikçileri sisteme tanımlanmıĢ ve gerekli olan üretim alt yapısı kontrol edilmiĢtir. ÇeĢnilerin üretim hattına uygunluğunu görebilmek adına üretim denemesi yapılmıĢtır. Yeni ürünler için etiket bilgileri hazırlanmıĢtır. Ayrıca duyusal, fiziksel, kimyasal testler yapılarak alerjen kontrolü ile çapraz bulaĢı riskleri hesaplanmıĢtır. Son olarak üretim metotları ve süreç parametreleri kesinleĢtirilerek seri üretime geçilmiĢ ve ürün müĢteriye sunulmuĢtur. Proje kapsamında geliĢtirilen üründe, geleneksel Türk tatlısının tadını çikolata ile birleĢtirip, tüketicilere her iki tatlının yeme deneyimini birlikte vermek hedeflenmiĢtir. Baklava standartlarını sağlamak amacıyla baklavayı oluĢturan bileĢenler ayrı ayrı seçilmiĢ ve çikolata ile karıĢtırıp bitmiĢ üründe hedeflenen tat ve yapı sağlanmıĢtır.

Baklava is one of the indispensable desserts of traditional Turkish cuisine. The definition of "Turkish Baklava" according to the Turkish Standards Institute; The dough containing flour, egg, salt, water and starch is opened in accordance with the technique and creamed inside or between, butter or plain oil obtained from butter and according to the type, pistachio, walnut, hazelnut or almond kernel is added and cut at the appropriate temperature. It is the product obtained by adding sherbet obtained by boiling water that has been cooked and cooked in a period of time, and finally granulated sugar and lemon juice or lemon salt has been added. If it is chocolate; It is a sweet food based on cocoa butter, cocoa mass, sugar and powders of dairy products depending on the type. One of the factors that will differentiate the product in the chocolate market, the first thing that comes to mind is the prescription of these main raw materials with the right combinations, then adding different flavors in certain proportions when this recipe becomes chocolate. When we look at the products in the market in general, nuts such as hazelnuts, pistachios and almonds are the leading products used as condiment. Damak brand is a brand with a high perception of premium combined with pistachio in the eyes of consumers. Pistachio, which is one of the first condiments that comes to mind when baklava is mentioned, forms the bond between Damak brand and baklava. Using this bond in the project, a chocolate dessert was presented to consumers by using seasonings and raw materials that will make consumers feel the experience of eating baklava. In the study, firstly the seasoning and raw materials were determined and preliminary samples were prepared. Afterwards, the shelf life tests of the product were carried out. The new seasoning suppliers were identified in the system and the necessary production infrastructure was checked. In order to see the suitability of the seasonings for the production line, a production trial was carried out. Label information has been prepared for new products. In addition, sensory, physical and chemical tests were performed and cross-contamination risks were calculated with allergen control. Finally, the production methods and process parameters were finalized and mass production was started and the product was presented to the customer. In the product developed within the scope of the project, it is aimed to combine the taste of traditional Turkish dessert with chocolate and to give consumers the experience of eating both sweets together. In order to meet the standards of baklava, the components that make up the baklava are selected separately and mixed with chocolate to provide the targeted taste and structure in the finished product.
The taste combining traditional turkish dessert baklava with chocolate: damak baklava
Keywords: Antep fıstığı; Baklava; Çikolata; Damak; Chocolate; Pistachio